Spinal Cord Injury and Related Clinical Trials - Kim, Young-Hoon (Clin Orthop Surg, 2017)
Spinal cord injury (SCI) has been considered an incurable condition and it often causes devastating sequelae. In terms of the pathophysiology of SCI, reducing secondary damage is the key to its treatment. Various researches and clinical trials have been performed, and some of them showed promising results; however, there is still no gold standard treatment with sufficient evidence. Two therapeutic concepts for SCI are neuroprotective and neuroregenerative strategies. The neuroprotective strategy modulates the pathomechanism of SCI. The purpose of neuroprotective treatment is to minimize secondary damage following direct injury. The aim of neuroregenerative treatment is to enhance the endogenous regeneration process and to alter the intrinsic barrier. With advancement in biotechnology, cell therapy using cell transplantation is currently under investigation. This review discusses the pathophysiology of SCI and introduces the therapeutic candidates that have been developed so far.